The Value Spread - Cohen, Randolph B.; Polk, Christopher; Vuolteenaho, Tuomo (Journal of Finance, 2003)
ABSTRACT We decompose the cross‐sectional variance of firms' book‐to‐market ratios using both a long U.S. panel and a shorter international panel. In contrast to typical aggregate time‐series results, transitory cross‐sectional variation in expected 15‐year stock returns causes only a relatively small fraction (20 to 25 percent) of the total cross‐sectional variance. The remaining dispersion can be explained by expected 15‐year profitability and persistence of valuation levels. Furthermore, this fraction appears stable across time and across types of stocks. We also show that the expected return on value‐minus‐growth strategies is atypically high at times when their spread in book‐to‐market ratios is wide.